Possibility of electronic data interchange to simplify work procedures (Case Study of Hilla Municipality Directorate) - كاظم علي سجاد; تناي غني دحام (Journal of Economics and Administrative Sciences, 2020)
Purpose: to demonstrate the possibility of moving to electronic data exchange dimensions (regulatory requirements, technical requirements, human requirements, senior management support) to simplify the work procedures dimensions (modern procedures, clarity of procedures, short procedures, availability of information and means required. The simplicity of the models used because of its importance to keep abreast of recent developments in the service of municipal works through the application of electronic data interchange, which simplifies procedures and out of the routine in the performance of the work of municipal departments has developed. It was applied to Municipality (Hilla) so that the transformation of the exchange of electronic data is to save time and reduce the expenses, thus the importance of these applications should be considered to raise the business of municipally provided to citizens. The study has developed two hypotheses for research. Design / Methodology / Approach: To achieve the objectives of the research, the researchers used the questionnaire as the main tool for collecting data, in addition to personal interviews with some employees of the municipality of Hilla Municipality. The sample included (69) individuals who occupy the position (department manager, division director), and these data were processed using the SPSS statistical package. Findings: The research reached a number of conclusions, the most important of which is that there is a clear vision in the sample of the study of the importance of moving towards electronic data interchange with its clear advantages in the development of working methods and procedures. Simple computerized management information systems are available that do not rise to the level of electronic exchange. The use of electronic exchange is limited to e-mail with some government agencies, and there is no type of electronic data exchange between departments of the municipality. Originality / Value: The current research provides a basis for adopting electronic data exchange and the most basic requirements as a tool to simplify work procedures and reduce red tape.